The mechanical rower: Construction, validity, and reliability of a test rig for wind braked rowing ergometers - Engleder, T.; Schulz, G.; Winkert, K.; Steinacker, J. M.; Treff, G. (Journal of Biomechanics, 2020)
Wind braked rowing ergometers are used worldwide for training and testing of rowers, but data on validity and reliability of the calculated mechanical power output are scarce. Studies published so far are based on data generated by human rowers, inevitably adding biological variability without any option to clamp particular variables like stroke structure or force. To this end, we developed a test rig for rowing ergometers aiming to generate valid and reliable stroke structures (i.e. force-displacement curves).